Preparation method of nano composite material for adsorbing potassium ions

By preparing nanocomposites, the problem of difficult separation of potassium ions in chemical high-salt wastewater is solved, efficient adsorption and resource recycling are achieved, and treatment costs are reduced.

CN119838559AInactive Publication Date: 2025-04-18XIAN SHANHAI SHULIAN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510072696.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Potassium ions are difficult to separate in chemical high-salt wastewater, and the existing processes are complex and costly, which affects resource recycling.

Method used

A nanocomposite material is prepared by mixing silicon source, aluminum source, template agent, structural guide agent and solvent to form a gel, and then through crystallization, drying, calcining and inorganic salt modification, a nanocomposite material with efficient adsorption of potassium ions is prepared.

Benefits of technology

It has achieved efficient adsorption of potassium ions, improved the wastewater purification effect, promoted the recycling and utilization of resources, and reduced the treatment cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838559A_ABST
    Figure CN119838559A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water treatment, and discloses a preparation method of a nano composite material for adsorbing potassium ions, the nano composite material has the advantages of wide raw material source, short process flow and reasonable and controllable production cost, can meet the requirements of industrial large-scale preparation, comprehensively considers the characteristics of chemical high-salinity wastewater, and is suitable for industrial production. By optimizing the raw material ratio, the gel formation and crystallization conditions and the inorganic salt modification process, the prepared nano composite material has a higher specific surface area and a more uniform pore structure, is high in potassium ion adsorption efficiency and high in selectivity, paves a way for realizing waste water resource reutilization, can be effectively regenerated and recycled after adsorption saturation, and has a wide application prospect. And the potassium-rich regenerated liquid can be recycled, so that the method has good economic benefits and social benefits in actual engineering projects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment, in particular to a method for preparing a nano composite material for adsorbing potassium ions. Background Art

[0002] Chemical high-salt wastewater refers to wastewater with a total salt content of at least 3.5wt%, which mainly comes from incomplete chemical reactions or by-products of chemical reactions in chemical production, especially a large amount of high COD, high-salt toxic wastewater generated in the production of chemical products such as coal chemical industry, petrochemical industry, metallurgy, fine chemicals, dyes, pesticides, etc., and mineralization caused by the addition of water treatment agents, acids and alkalis during wastewater treatment, as well as the concentrate produced by the recovery of most "fresh water". Direct discharge of chemical high-salt wastewater into natural water bodies will cause water pollution, harm aquatic organisms, and affect the ecological balance.

[0003] After the chemical high-salt wastewater is treated by the "zero emission system", the mass fraction of total dissolved solids (TDS) in the concentrated water is often greater than 5%. The concentrated water is further treated by the salt separation crystallization process to obtain recyclable by-product salts, namely sodium sulfate and sodium chloride. However, the salt separation crystallization process will produce mother liquor, and the salt content of the mother liquor is greater than 20wt%, which contains monovalent salts such as mixed potassium nitrate, potassium chloride, sodium chloride, sodium nitrate and other impurities. At present, the common practice in the chemical industry is to use evaporation and crystallization to produce miscellaneous salts. These miscellaneous salts are hazardous wastes, accounting for 15-25% of the total salt content, with high disposal costs, which brings a large economic burden to chemical companies.

[0004] As a natural potassium-containing mineral, potassium salt has the characteristics of high solubility and is mostly soluble in water. Potassium salt has certain resource properties and can be recycled. However, due to the variability and concealment of potassium salt and the complexity of wastewater components, it is difficult to effectively separate potassium salt from wastewater during the recycling process. The recycling process is complicated, separation is difficult and expensive, and product quality will be affected.

[0005] In this context, nanocomposites have attracted much attention due to their unique physical and chemical properties. Nanomaterials have a high surface-to-volume ratio and chemical activity, as well as specific morphology and size effects. These characteristics make nanomaterials have potential application value in adsorption, separation and other fields. At the same time, the controllable synthesis and effective assembly of nanomaterials, as well as the functional design and performance research based on nanomaterials have become the premise and guarantee for the practical application of related materials. However, although nanomaterials have shown great application potential in many fields, there are few reports on the adsorption of potassium ions in high-salt wastewater. This may be due to problems such as cumbersome preparation process, difficult functional design, unstable structure and poor pore control.

[0006] In summary, the application of nanomaterials in the adsorption of potassium ions in high-salinity wastewater not only helps to solve the current problems in the treatment of high-salinity wastewater in the chemical industry, but also enables the effective recycling and utilization of resources, which has important economic and environmental significance. Therefore, the development of a nanocomposite material preparation technology suitable for the adsorption of potassium ions in high-salinity wastewater is of great significance for promoting the sustainable development of the chemical industry. Summary of the invention

[0007] 1. Technical issues to be resolved

[0008] In order to solve the above technical problems, the present invention provides a method for preparing a nanocomposite material for adsorbing potassium ions, and provides a method for preparing a stable and reliable adsorbent in engineering practice, which solves the problem that potassium ions are difficult to separate in high-salt wastewater, and paves the way for wastewater purification and resource recycling.

[0009] (II) Technical solution

[0010] In order to achieve the above object, the present invention discloses a method for preparing a nanocomposite material for adsorbing potassium ions, comprising the following steps:

[0011] Step (1), mixing a silicon source, an aluminum source, a template, a structure directing agent and a solvent, reacting them in an alkaline environment at room temperature, and obtaining a gel after the reaction is completed;

[0012] Step (2), transferring the gel obtained in step (1) to a reaction kettle, heating, crystallizing, cooling after crystallization, centrifuging, washing with deionized water until neutral, placing in an oven, vacuum drying, vacuum drying using a vacuum nitrogen-filled oven at 80-100° C. to dry to a moisture content of less than 3%, and grinding after vacuum drying to obtain a solid powder;

[0013] Step (3), calcining the solid powder obtained in step (2) under a protective gas atmosphere to obtain a nanomaterial;

[0014] Step (4), modifying the nanomaterial obtained in step (3) with inorganic salts, washing it after modification, and drying it in an oven at 80-100° C. until the moisture content is less than 1%, thereby obtaining a nanocomposite material that absorbs potassium ions.

[0015] Preferably, in the step (1), the molar ratio of the silicon source is calculated as SiO2, the molar ratio of the aluminum source is calculated as Al2O3, and the molar ratio of the silicon source, the aluminum source, the template, the structure directing agent and the solvent is (1.5-3):(0.15-0.3):(0.2-0.5):(0.1-0.35):(25-50).

[0016] Preferably, the silicon source in step (1) is composed of an organic silicon source and an inorganic silicon source in a molar ratio of (3-6):1.

[0017] Preferably, the organic silicon source in the silicon source includes any one or two of methylchlorosilane, phenylchlorosilane, methylvinylchlorosilane, ethyltrichlorosilane, propyltrichlorosilane, vinyltrichlorosilane and γ-chloropropyltrichlorosilane.

[0018] Preferably, the inorganic silicon source in the silicon source includes any one or two of silicon tetrachloride, colloidal silicon dioxide, silica gel, white carbon black, and water glass.

[0019] Preferably, the aluminum source in step (1) is an aluminum carboxylate salt, and the aluminum carboxylate salt includes any one or two of aluminum p-aminobenzoate, aluminum vinyl carboxylate, aluminum anthranilate, aluminum isopropoxide carboxylate, and aluminum terephthalate.

[0020] Preferably, in step (1), the template agent is a quaternary ammonium ionic liquid, and the quaternary ammonium ionic liquid includes any one or two of propyltrimethylammonium bromide, butyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, and triethylmethylammonium chloride.

[0021] Preferably, the structure directing agent in step (1) is an organic structure directing agent, and the organic structure directing agent includes any one or two of hydroxyethyltrimethylamine hydroxide, diisopropylamine, dipropylamine, n-butylamine, and hexamethylenetetramine.

[0022] Preferably, the solvent in step (1) consists of an organic solvent and deionized water.

[0023] Preferably, in step (1), the molar ratio of the organic solvent to deionized water is 1:5.

[0024] Preferably, the organic solvent in the solvent includes any one or two of xylene, cyclohexanone, cyclohexanol and dimethyl sulfoxide.

[0025] Preferably, the alkaline condition in step (1) is pH=14, which is adjusted by using a sodium hydroxide aqueous solution with a mass fraction of 30%.

[0026] Preferably, the reactor in step (2) is a hydrothermal reactor, the inner lining of which is made of PTFE material, the heating rate of which is 1-3°C / min, the crystallization is constant temperature crystallization, the control temperature is 100-120°C, and the constant temperature crystallization time is 12-24h.

[0027] Preferably, the feeding coefficient in the reactor in step (2) is less than 0.8.

[0028] Preferably, the stirring rate of the reactor in step (2) is 30-60 r / min.

[0029] Preferably, the reaction kettle is cooled in step (2) by passing water or cooling medium.

[0030] Preferably, the grinding process in step (2) uses a grinder or a mortar.

[0031] Preferably, the calcination process in step (3) is carried out in a calcination furnace, the protective atmosphere is a nitrogen atmosphere or an argon atmosphere, the calcination heating rate is 2-5°C / min, the calcination temperature is 500-550°C, and the calcination time is 4-6h.

[0032] Preferably, the roasting process in step (3) is carried out in a roasting furnace, and the roasting furnace includes one of a rotary atmosphere furnace, a nitrogen-filled muffle furnace, and an electric heating drum furnace.

[0033] Preferably, the modification process in step (4) is as follows: the nanomaterial obtained in step (3) is completely immersed in a saturated inorganic salt solution and boiled, the pH value of the saturated inorganic salt solution is 6-9, the boiling time is 1-2h, cooled to room temperature, boiled again, and the boiling is repeated three times under the same conditions.

[0034] Preferably, the inorganic salt in step (4) comprises one of sodium chloride, ammonium chloride, barium chloride and strontium chloride.

[0035] Preferably, the cleaning in step (4) is carried out by stirring at room temperature.

[0036] (III) Beneficial technical effects

[0037] Compared with the prior art, the present invention has the following chemical mechanisms and beneficial technical effects:

[0038] (1) The present invention uses a combination of an organic silicon source and an inorganic silicon source, with organic silicon monomer as the main component and inorganic silicon as a supplement. At the same time, a specific carboxylic acid aluminum salt is used as an aluminum source, which can optimize the structure and performance of the gel, help to form a more uniform and stable gel structure, and use ionic liquid as a template to make the pore size of the nanomaterial uniform, thereby ensuring the dispersibility of the active sites. The organic structure directing agent further guides the crystallization process of the material to ensure the formation of a nanostructure with efficient adsorption performance. By adjusting the silicon-aluminum ratio, the compatibility and selectivity of the nanomaterial are optimized, and the adsorption amount is significantly improved. The nanomaterial is modified using a saturated solution of an inorganic salt. The process of repeated boiling and cooling helps the inorganic salt to fully penetrate into the material, ensuring the uniformity and effectiveness of the modification. Through ion exchange or adsorption, the charge distribution and pore structure on the surface of the material are changed, thereby improving its selective adsorption capacity for potassium ions.

[0039] (2) The raw material sources of the present invention are wide, the process flow is short, the production cost is reasonable and controllable, and it can meet the requirements of industrial scale-up preparation. By optimizing the raw material ratio, gel formation and crystallization conditions, and inorganic salt modification process, the prepared nanocomposite material has a higher specific surface area and a more uniform pore structure, thereby improving the adsorption capacity and selectivity for potassium ions. Taking into account the characteristics of high-salt wastewater, the preparation path is innovated to provide technical support for the resource utilization of high-salt wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0041] Figure 1 The present invention is a process flow chart for preparing a nanocomposite material for adsorbing potassium ions. DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0043] Example 1

[0044] A method for preparing a nanocomposite material for adsorbing potassium ions comprises the following steps:

[0045] (1) mixing a silicon source, an aluminum source, a template, a structure-directing agent and a solvent in a molar ratio of 1.5:0.3:0.2:0.35:25, wherein the molar ratio of the silicon source is SiO2, the molar ratio of the aluminum source is Al2O3, the silicon source is composed of an organic silicon source methylchlorosilane and an inorganic silicon source silicon tetrachloride in a molar ratio of 3:1, the aluminum source is aluminum p-aminobenzoate, the template is propyltrimethylammonium bromide, the structure-directing agent is hydroxyethyltrimethylammonium hydroxide, and the solvent is composed of xylene and deionized water in a molar ratio of 1:5, reacting in an alkaline environment at room temperature, adjusting the pH to 14 with a 30% by mass sodium hydroxide aqueous solution, and obtaining a gel after the reaction is completed;

[0046] (2) The gel is transferred to a hydrothermal reactor, which is lined with PTFE material and has a feed coefficient of 0.7. The temperature is raised and crystallized. During the crystallization process, the crystallization temperature rise rate is 1°C / min, the crystallization is constant temperature crystallization, the control temperature is 100°C, the constant temperature crystallization time is 12h, and the stirring rate of the hydrothermal reactor is 30r / min. After the crystallization is completed, the gel is cooled by passing water coolant, centrifuged, washed with deionized water until neutral, placed in an oven, and vacuum dried. The vacuum drying is carried out in a vacuum nitrogen-filled oven at 80°C until the moisture content is less than 3%. After vacuum drying, the gel is ground with a grinder to obtain a solid powder.

[0047] (3) calcining the solid powder in a nitrogen atmosphere, using a rotary atmosphere furnace, with a heating rate of 2°C / min, a temperature of 500°C, and a calcination time of 4h to obtain a nanomaterial;

[0048] (4) The nanomaterial is modified with inorganic salts. During the modification process, the nanomaterial is completely immersed in a saturated sodium chloride solution and boiled. The pH value of the saturated sodium chloride solution is 6. The boiling time is 1 hour. The nanomaterial is cooled to room temperature and boiled again. The boiling is repeated three times under the same conditions. After the modification is completed, the nanomaterial is placed in a special cleaning tank and stirred and cleaned at room temperature. The nanomaterial is dried in an oven and dried at 80° C. until the moisture content is less than 1%, thereby obtaining a nanocomposite material that adsorbs potassium ions.

[0049] Example 2

[0050] A method for preparing a nanocomposite material for adsorbing potassium ions comprises the following steps:

[0051] (1) mixing a silicon source, an aluminum source, a template, a structure directing agent and a solvent in a molar ratio of 3:0.15:0.5:0.1:50, wherein the molar ratio of the silicon source is SiO2, the molar ratio of the aluminum source is Al2O3, the silicon source is composed of an organic silicon source phenylchlorosilane and an inorganic silicon source colloidal silica in a molar ratio of 6:1, the aluminum source is vinyl carboxylate aluminum, the template is butyltrimethylammonium chloride, the structure directing agent is diisopropylamine, and the solvent is composed of cyclohexanone and deionized water in a molar ratio of 1:5, reacting in an alkaline environment at room temperature, adjusting the pH to 14 with a 30% by mass sodium hydroxide aqueous solution, and obtaining a gel after the reaction is completed;

[0052] (2) The gel is transferred to a hydrothermal reactor, which is lined with PTFE material and has a feed coefficient of 0.75. The temperature is increased and crystallized. During the crystallization process, the temperature increase rate of the crystallization is 3°C / min, the crystallization is constant temperature crystallization, the control temperature is 120°C, the constant temperature crystallization time is 24h, and the stirring rate of the hydrothermal reactor is 60r / min. After the crystallization is completed, the temperature is cooled by passing water coolant, centrifuged, washed with deionized water to neutrality, placed in an oven, and vacuum dried. The vacuum drying is carried out in a vacuum nitrogen-filled oven at 100°C to dry to a moisture content of less than 2%. After vacuum drying, the solid powder is ground by a grinder to obtain a solid powder;

[0053] (3) calcining the solid powder in a nitrogen atmosphere using a nitrogen-filled muffle furnace at a heating rate of 5° C. / min, at a temperature of 550° C., for 6 h, to obtain a nanomaterial;

[0054] (4) The nanomaterial is modified with inorganic salts. During the modification process, the nanomaterial is completely immersed in a saturated ammonium chloride solution and boiled. The pH value of the saturated ammonium chloride solution is 9. The boiling time is 2 hours. The nanomaterial is cooled to room temperature and boiled again. The boiling is repeated three times under the same conditions. After the modification is completed, the nanomaterial is placed in a special cleaning tank and stirred and cleaned at room temperature. The nanomaterial is dried in an oven and dried at 100° C. until the moisture content is less than 1%, thereby obtaining a nanocomposite material that adsorbs potassium ions.

[0055] Embodiment 3:

[0056] A method for preparing a nanocomposite material for adsorbing potassium ions comprises the following steps:

[0057] (1) mixing a silicon source, an aluminum source, a template, a structure-directing agent and a solvent in a molar ratio of 2.25:0.225:0.35:0.225:37.5, wherein the molar ratio of the silicon source is SiO2, the molar ratio of the aluminum source is Al2O3, the silicon source is composed of an organic silicon source methylvinylchlorosilane and an inorganic silicon source white carbon black in a molar ratio of 4.5:1, the aluminum source is aluminum anthranilate, the template is hexadecyltrimethylammonium bromide, the structure-directing agent is hexamethylenetetramine, and the solvent is composed of dimethyl sulfoxide and deionized water in a molar ratio of 1:5, reacting in an alkaline environment at room temperature, adjusting the pH to 14 with a 30% by mass sodium hydroxide aqueous solution, and obtaining a gel after the reaction is completed;

[0058] (2) The gel is transferred to a hydrothermal reactor, which is lined with PTFE material and has a feeding coefficient of 0.7. The temperature is raised and crystallized. During the crystallization process, the crystallization temperature rise rate is 2°C / min, the crystallization is constant temperature crystallization, the control temperature is 110°C, the constant temperature crystallization time is 18h, and the stirring rate of the hydrothermal reactor is 45r / min. After the crystallization is completed, the gel is cooled by passing water coolant, centrifuged, washed with deionized water until neutral, placed in an oven, and vacuum dried. The vacuum drying is carried out in a vacuum nitrogen-filled oven at 90°C until the moisture content is less than 1%. After vacuum drying, the gel is ground with a grinder to obtain a solid powder.

[0059] (3) calcining the solid powder in a nitrogen atmosphere using a nitrogen-filled muffle furnace at a heating rate of 3.5° C. / min, at a temperature of 525° C., for 5 h, to obtain a nanomaterial;

[0060] (4) The nanomaterial is modified with inorganic salts. During the modification process, the nanomaterial is completely immersed in a saturated barium chloride solution and boiled. The pH value of the saturated barium chloride solution is 7.5. The boiling time is 1.5 hours. The nanomaterial is cooled to room temperature and boiled again. The boiling is repeated three times under the same conditions. After the modification is completed, the nanomaterial is placed in a special cleaning tank and stirred and cleaned at room temperature. The nanomaterial is dried in an oven at 90° C. until the moisture content is less than 1%, thereby obtaining a nanocomposite material that adsorbs potassium ions.

[0061] The water quality of the salt crystallization mother liquor (i.e. "crystallization mother liquor") of a coal chemical high-salt wastewater is as follows: inert organic matter (inert COD) is 11200 mg / L, TDS is 205600 mg / L, total hardness (calculated as CaCO3) is 1330 mg / L, potassium ion is 3470 mg / L, nitrate is 2860 mg / L, chloride ion is 70840 mg / L, sulfate ion is 49600 mg / L, pH=12.7, total silicon (calculated as SiO2) is 477 mg / L.

[0062] The water quality of the above-mentioned coal chemical wastewater salt crystallization mother liquor is that it contains inert COD, Na + , K + , Ca 2+ Mg 2+ 、NO3 - , Cl - 、SO4 2- The potassium ions in the multi-component complex system can be separated and recovered by the nano-composite material obtained by the preparation method of the present invention.

[0063] The nanocomposite material for adsorbing potassium ions prepared in Examples 1-3 of the present invention was used as a sample to perform adsorption treatment on a mother liquor of salt crystallization of high-salt wastewater from a coal chemical industry. 1L of the mother liquor was taken and 0.5L of the nanocomposite material for adsorbing potassium ions obtained by the preparation method of the present invention was added. The adsorption time and the content of potassium ions before and after adsorption were recorded, and the removal rate of potassium ions was calculated. The specific test results are shown in Table 1:

[0064] Table 1

[0065]

[0066] According to the test results in Table 1, it can be seen that the potassium ion-adsorbing nanocomposite materials prepared in Examples 1-3 have a high removal rate for potassium ions in the high-salt wastewater salt crystallization mother liquor, and the potassium ion-adsorbing nanocomposite materials corresponding to Example 2 can achieve a removal rate of 92.45% for potassium ions in the high-salt wastewater salt crystallization mother liquor.

[0067] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A method for preparing a nanocomposite material for adsorbing potassium ions, characterized in that: The following steps are involved: Step (1), mixing a silicon source, an aluminum source, a template, a structure directing agent and a solvent, reacting them under alkaline conditions, and obtaining a gel after the reaction is completed; Step (2), transferring the gel obtained in step (1) into a reaction kettle, heating, crystallizing, cooling after the crystallization, centrifuging, washing to neutrality, drying, grinding, and obtaining a solid powder; Step (3), calcining the solid powder obtained in step (2) under a protective gas atmosphere to obtain a nanomaterial; Step (4), modifying the nanomaterial obtained in step (3) with inorganic salts, washing and drying the nanomaterial after the modification, to obtain a nanocomposite material that adsorbs potassium ions.

2. The method for preparing a nanocomposite material for adsorbing potassium ions according to claim 1, wherein: In the step (1), the molar ratio of the silicon source is calculated as SiO2, the molar ratio of the aluminum source is calculated as Al2O3, and the molar ratio of the silicon source, the aluminum source, the template, the structure directing agent and the solvent is (1.5-3):(0.15-0.3):(0.2-0.5):(0.1-0.35):(25-50).

3. The method for preparing a nanocomposite material for adsorbing potassium ions according to claim 1, characterized in that: In the step (1), the silicon source is composed of an organic silicon source and an inorganic silicon source in a molar ratio of (3-6):1; The organosilicon source includes any one or two of methylchlorosilane, phenylchlorosilane, methylvinylchlorosilane, ethyltrichlorosilane, propyltrichlorosilane, vinyltrichlorosilane, and γ-chloropropyltrichlorosilane; The inorganic silicon source includes any one or two of silicon tetrachloride, colloidal silicon dioxide, silica gel, white carbon black, and water glass.

4. The method for preparing a nanocomposite material for adsorbing potassium ions according to claim 1, characterized in that: In the step (1), the aluminum source is an aluminum carboxylate salt, and the aluminum carboxylate salt includes any one or two of aluminum p-aminobenzoate, aluminum vinyl carboxylate, aluminum anthranilate, aluminum isopropoxide carboxylate, and aluminum terephthalate; The template agent is a quaternary ammonium ionic liquid, and the quaternary ammonium ionic liquid includes any one or two of propyltrimethylammonium bromide, butyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, and triethylmethylammonium chloride; The structure directing agent is an organic structure directing agent, and the organic structure directing agent includes any one or two of hydroxyethyltrimethylamine hydroxide, diisopropylamine, dipropylamine, n-butylamine, and hexamethylenetetramine.

5. The method for preparing a nanocomposite material for adsorbing potassium ions according to claim 1, characterized in that: The solvent in step (1) is composed of an organic solvent and deionized water, and the organic solvent includes any one or two of xylene, cyclohexanone, cyclohexanol, and dimethyl sulfoxide.

6. The method for preparing a nanocomposite material for adsorbing potassium ions according to claim 1, characterized in that: The reactor in step (2) is a hydrothermal reactor, the inner lining of which is made of PTFE material, the heating rate of which is 1-3°C / min, the crystallization is constant temperature crystallization, the control temperature is 100-120°C, and the constant temperature crystallization time is 12-24h.

7. The method for preparing a nanocomposite material for adsorbing potassium ions according to claim 1, characterized in that: The calcination process in step (3) is carried out in a calcination furnace, the protective atmosphere is a nitrogen atmosphere or an argon atmosphere, the calcination heating rate is 2-5°C / min, the calcination temperature is 500-550°C, and the calcination time is 4-6h.

8. The method for preparing a nanocomposite material for adsorbing potassium ions according to claim 7, characterized in that: The roasting furnace in step (3) includes a rotary atmosphere furnace, a nitrogen-filled muffle furnace, and an electric heating drum furnace.

9. The method for preparing a nanocomposite material for adsorbing potassium ions according to claim 1, characterized in that: The modification process in step (4) is as follows: the nanomaterial obtained in step (3) is completely immersed in a saturated inorganic salt solution and boiled, the pH value of the saturated inorganic salt solution is 6-9, the boiling time is 1-2 hours, cooled to room temperature, boiled again, and the boiling is repeated three times under the same conditions.

10. The method for preparing a nanocomposite material for adsorbing potassium ions according to claim 9, characterized in that: The inorganic salt in step (4) includes one of sodium chloride, ammonium chloride, barium chloride and strontium chloride.